Critical Analysis of the Development of the Design of Lattice Tube Concrete Bridges with a Ride on Top - Spivak, D. S.; Kliuchnyk, S. V. (Science and Transport Progress, 2024)
Purpose. The paper aims to highlight and substantiate the need to find rational design schemes for lattice tube concrete bridges with a ride on top based on the analysis of recent research and regulatory documents. Methodology. The current scientific research is analyzed to determine the current state of development of pipe concrete lattice structures. Methods for improving structures are presented. Combinations of filling the grating elements with concrete, variants of cross-sections of the grating elements, their advantages and disadvantages are analyzed. The state of building codes of Ukraine and other countries is considered in order to determine possible options for the design of pipe concrete bridge structures. Due to the lack of detailed research on this issue, the feasibility of implementing optimization studies for these structures and the steps necessary for this are determined. Findings. The optimization of pipe-concrete bridge structures is a relevant area of research, but it requires a multicomponent approach and the use of modern computer facilities. The method of linear optimization is proposed and its general steps for finding economic models are determined. It was found that the base of Ukrainian SCSs in the field of pipe and concrete structures is limited, but can be expanded by using European standards and other international regulations. Originality. The necessity of global development and improvement of pipe concrete gratings of bridge spans is highlighted. Attention is focused on the advantages of this area, which contributes to decision-making at the stage of selecting the type of bridge and detailed design of pipe-concrete lattice bridges. A methodology for finding the optimal grids is proposed, which can integrate existing methods of structural improvement and the requirements of regulatory documents. Practical value. The results of the study can be used to improve the design of pipe concrete bridges at the design stage. Optimization of gratings can help to increase the efficiency of construction and reliability of this type of bridge structure.